2018
DOI: 10.7554/elife.39111
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic reticular control of local sleep in mouse sensory cortex

Abstract: Sleep affects brain activity globally, but many cortical sleep waves are spatially confined. Local rhythms serve cortical area-specific sleep needs and functions; however, mechanisms controlling locality are unclear. We identify the thalamic reticular nucleus (TRN) as a source for local, sensory-cortex-specific non-rapid-eye-movement sleep (NREMS) in mouse. Neurons in optogenetically identified sensory TRN sectors showed stronger repetitive burst discharge compared to non-sensory TRN cells due to higher activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(154 citation statements)
references
References 86 publications
9
140
0
Order By: Relevance
“…Interestingly, oscillatory activity in Drosophila R5 neurons is reminiscent of up-and down-states occurring at the level of mammalian cortical networks during deep sleep [36]. We thus hypothesize that the oscillations observed here are comparable to sleep-regulating thalamocortical oscillations [37][38][39] as well as network-specific oscillations observed during sleep deprivation in vertebrates (local sleep) [2,40,41]. Thus, the R5 network could be functionally analogous to the thalamus, as network-specific synchronization of slowwave activity within the thalamus plays a crucial role in maintaining sleep [37][38][39] and sensory gating [42].…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, oscillatory activity in Drosophila R5 neurons is reminiscent of up-and down-states occurring at the level of mammalian cortical networks during deep sleep [36]. We thus hypothesize that the oscillations observed here are comparable to sleep-regulating thalamocortical oscillations [37][38][39] as well as network-specific oscillations observed during sleep deprivation in vertebrates (local sleep) [2,40,41]. Thus, the R5 network could be functionally analogous to the thalamus, as network-specific synchronization of slowwave activity within the thalamus plays a crucial role in maintaining sleep [37][38][39] and sensory gating [42].…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, local aspects of spindles at the thalamic level is further supported by the possible occurrence of local spindles within the mouse TRN itself (Fernandez et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al . (2017, 2018) have recently shown in mice that cells in the TRN sector corresponding to auditory cortex had less repetitive bursting capacities than cells in other TRN sectors (reviewed by Vantomme et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Applied to the mouse, the SO (or δ1) upper demarcation might be as high as 2.5Hz, as others have already assumed due to other considerations (Binder et al, 2012, Fernandez et al, 2018. Accordingly, the δ1 population of SWs we identified, could represent the SO while δ2 SWs could represent δ, albeit with species-specific lower and upper frequency boundaries.…”
Section: Two Populations Of Swsmentioning
confidence: 58%
“…For instance, cortical UP-states synchronize thalamic δoscillations (Steriade et al, 1991), which might contribute to the prominent nesting we observed of δ2-waves at δ1 onset, while excitatory thalamocortical input to the cortex can trigger cortical UP-state initiation and removing thalamic input reduces cortical SO period and synchrony (David et al, 2013, Lemieux et al, 2014, Gent et al, 2018a. Moreover, thalamic neurons are intrinsically capable of generating rhythmic oscillations at <1Hz frequencies (Blethyn et al, 2006, Crunelli et al, 2018, Fernandez et al, 2018, Halasz et al, 2014, Herrera et al, 2016 that could aid the strengthening of the cortical SO. These and other observations demonstrate that SWs must be regarded as an emerging property of the thalamocortical network acting as a single unit (Crunelli et al, 2015).…”
Section: Neuronal Substrates Of δ1 and δ2mentioning
confidence: 86%